ANALISIS IMPLEMENTASI KEBIJAKAN PELAYANAN PARKIR DI TEPI JALAN UMUM KOTA SEMARANG PADA TAHUN 2024 - Fakhrul Khairun Abas; Puji Astut (Journal of Politic and Government Studies, 2026)
This study examines the arrangement of parking in Semarang City which is a strategic part of the implementation of urban transportation policies that have a direct effect on traffic order, urban spatial planning, and the optimization of Regional Original Revenue in the midst of the rapid growth in the number of motor vehicles in Semarang City in 2024. However, even though it has been regulated through Mayor Regulation Number 70 of 2021 and other supporting regulations, the implementation of the parking policy in 2024 still faces various problems such as limited parking spaces, rampant illegal parking, levy leakage, and low service quality. This study aims to analyze the implementation of the parking service policy by the Semarang City Government through the Transportation Department in 2024 and identify supporting and inhibiting factors in its implementation. This study uses a descriptive qualitative method (Sugiyono, 2014) by taking data through interviews, observations, and documentation. As for this study, to analyze the implementation of parking service policies in Semarang City is carried out with the approach of Van Metter, & Van Horn (1975). The results of this study show that the implementation of Semarang Mayor Regulation Number 70 of 2021 in parking services in 2024 has not been running optimally, even though it has been supported by a legal basis, clear policy standards, resources, and relatively good coordination between stakeholders. Various technical, social, and institutional obstacles such as the unpreparedness of human resources, limited use of e-parking technology, community resistance, and the existence of illegal parking attendants cause the goals of improving service quality, transparency, and optimization of PAD have not been achieved, which is reflected in the low realization of parking levies.